Subcontractor Selection and Risk Analysis Using Failure Mode Effect Analysis (FMEA) and Analytic Network Process (ANP) Methods (Case Study at PT. XYZ) - Prayogi, Arie; Suparno, Suparno (CV. Utility Project Solution, 2023)
Selecting the right subcontractor for construction work is one of the keys to project success. Therefore, selecting subcontractors requires the right decision. This research aims to create a model for selecting subcontractors for bored pile work by considering the risks of subcontractors by integrating Analytic Network Process (ANP) and FMEA methods at PT XYZ. There are 7 criteria and 13 sub-criteria for boredpile subcontractors that have been confirmed by experts. Meanwhile, the criteria used include cost, working experience, quality, technical, HSE record, productivity, and financial ability. In addition, there are 8 identified risks to subcontractors from 7 criteria. Based on the results of the integration of the ANP and FMEA methods, it produces priority for subcontractor B with a score of 0.7021, subcontractor A with a score of 0. 6151 and subcontractor C with a score of 0.5524. From the results of the ANP and FMEA integration calculations, subcontractor B is a borepile work subcontractor that complies with the criteria for selecting the right subcontractor and has a low risk compared to other subcontractors.